Telling Stories About Farming: Mediated Authenticity and New Zealand's Country Calendar. (January 2022) - Fountaine, Susan; Bulmer, Sandy
Mediated authenticity in New Zealand's Country Calendar ( CC ) television program is explored from the perspective of its producers, and rural and urban audiences. Paradoxically, CC is understood as both "real" and "honest" television and a constructed, idyllic version of the rural good life in New Zealand. Techniques and devices such as a predictable narrative arc, consistent narration, invisible reporting and directing, and naturalized sound and vision contribute to the show's predictability, ordinariness, spontaneity and im/perfection, mediating an authentic yet aspirational view of farming life. We elucidate how factual, primetime television contributes to a shared national sense of "who we are" while navigating different audience experiences and expectations. At stake is New Zealanders' attachment to rural identity, which underpins public policy commitments to the farming sector, at a time when new agricultural politics are increasingly contested.